2006
DOI: 10.1063/1.2185468
|View full text |Cite
|
Sign up to set email alerts
|

Highly efficient top emitting organic light-emitting diodes with organic outcoupling enhancement layers

Abstract: We demonstrate high-efficiency top emitting organic light-emitting diodes employing silver (Ag) for both anode and cathode. Following the p-i-n doping and double emission layer concepts, the devices show a very high efficiency of 50cd∕A at 1000cd∕m2 with a driving voltage of only 2.85V. The efficiency can be further improved to 78cd∕A by tuning the optical structure with an organic capping layer. A simple explanation based on the transmittance of the top contact cannot explain this efficiency enhancement. Inst… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

2
75
0

Year Published

2007
2007
2016
2016

Publication Types

Select...
4
4

Relationship

1
7

Authors

Journals

citations
Cited by 119 publications
(77 citation statements)
references
References 12 publications
2
75
0
Order By: Relevance
“…1-4 Through harvesting of both singlet and triplet excitons, the external quantum efficiency ͑ ext ͒ of PhOLEDs has reached above 20% by using the optimized material systems, 5-7 p-i-n structures, 8,9 and microcavity structures.…”
mentioning
confidence: 99%
See 2 more Smart Citations
“…1-4 Through harvesting of both singlet and triplet excitons, the external quantum efficiency ͑ ext ͒ of PhOLEDs has reached above 20% by using the optimized material systems, 5-7 p-i-n structures, 8,9 and microcavity structures.…”
mentioning
confidence: 99%
“…1-4 Through harvesting of both singlet and triplet excitons, the external quantum efficiency ͑ ext ͒ of PhOLEDs has reached above 20% by using the optimized material systems, [5][6][7] p-i-n structures, 8,9 and microcavity structures. 10,11 However, the efficiency roll-off ͑the decrease of efficiency with increasing current density͒ occurs at much lower luminance than required in displays or solid-state lighting.…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…In contrast, aromatic molecules such as ortho-chloranil, TCNQ, and dicyano-p-benzoquinone (DDQ) were used in doping phthalocyanines, stacked phthalocyanines, and oligothiophenes [463][464][465][466][467] but less effectively. In the last few years, systematic investigations were carried out to understand the underlying doping physics, which led to the development of OLEDs [468][469][470][471][472][473][474][475][476][477][478][479][480][481].…”
Section: Impurity-doped Os P-n Junctionsmentioning
confidence: 99%
“…This enhances light outcoupling to some extent, even though it does not completely solve the problem of TIR. [10][11][12] Thomschke et al 13 demonstrated the lamination of a high refractive index microlens foil on top of a white OLED and obtained a device efficacy of over 30 lm/W (27% EQE). Recently, Kim et al achieved an EQE of 44.7% (1.8-fold enhancement) for a green top-emitting OLED using a microlens array that was fabricated by evaporating an organic capping layer through a shadow mask.…”
mentioning
confidence: 99%